Practice of using the «Letter of forgiveness» method for solving emotional problems (The Journal of Psychology and Sociology, 2021)
The article is written about the reason of resentment occurrence and the importance of forgiveness for a person. Described the «Letter of Forgiveness» technique and student reviews are written after the technique has been completed. The study involved 1st year students, the most interesting responses are given below. Objective of the study: to analyze forgiveness from different points of view and to test the effect of forgiveness on emotional state. Object of research: 24 students, forgiveness is considered as a subject. The general hypothesis is that forgiveness has a positive effect on the emotional state. The article discusses the consequences of accumulating grievances, touches on the reason for their occurrence and describes the main benefits of forgiveness. Forgiveness is an emotion regulation process that is important for both physical and mental health. Given these benefits, it’s important to learn how to forgive. This technique helps to reduce the level of negative emotions, analyze your behavior and free yourself from the past, which is confirmed by student reviews. All reviews were positive. This technique has a positive effect on any age. It is a very good tool for maintaining a positive attitude and emotional balance. The conclusions of the article reflect the results of the research and student reviews.Key words: resentment, forgiveness, «letter of forgiveness» technique, emotional balance.